Development and Preliminary Validation of the Divine Connectedness Scale in the USA - Datu, Jesus Alfonso D. (Journal of religion and health, 2024)
This research conceptualized and offered preliminary evidence on the psychometric properties of the 10-item Divine Connectedness Scale—a measure that assesses individuals’ perceptions of feeling supported by (divine guidance) and working with (divine collaboration) God or a Supreme Being. Results of exploratory factor analysis and confirmatory factor analysis with 434 undergraduate students in the United States showed that scores from a single-factor model of divine connectedness were valid and reliable. Divine connectedness was positively associated with religiosity, forgiveness, and well-being variables. Divine connectedness showed incremental validity over demographic covariates, social desirability, and religiosity in predicting later meaning in life and flourishing.